Comparison of Simplexa Universal Direct PCR with Cytotoxicity Assay for Diagnosis of Clostridium difficile Infection: Performance, Cost, and Correlation with Disease - Landry, Marie L. (American Society for Microbiology, 2014)
Simplexa Clostridium difficile universal direct PCR, a real-time PCR assay for the detection of the C. difficile toxin B (tcdB) gene using the 3M integrated cycler, was compared with a two-step algorithm which includes the C. Diff Chek-60 glutamate dehydrogenase (GDH) antigen assay followed by cytotoxin neutralization. Three hundred forty-two liquid or semisolid stools submitted for diagnostic C. difficile testing, 171 GDH antigen positive and 171 GDH antigen negative, were selected for the study. All samples were tested by the C. Diff Chek-60 GDH antigen assay, cytotoxin neutralization, and Simplexa direct PCR. Of 171 GDH-positive samples, 4 were excluded (from patients on therapy or from whom duplicate samples were obtained) and 88 were determined to be true positives for toxigenic C. difficile. Of the 88, 67 (76.1%) were positive by the two-step method and 86 (97.7%) were positive by PCR. Seventy-nine were positive by the GDH antigen assay only. Of 171 GDH antigen-negative samples, none were positive by PCR. One antigen-negative sample positive by the cytotoxin assay only was deemed a false positive based on chart review. Simplexa C. difficile universal direct PCR was significantly more sensitive for detecting toxigenic C. difficile bacteria than cytotoxin neutralization (P = 0.0002). However, most PCR-positive/cytotoxin-negative patients did not have clear C. difficile disease. The estimated cost avoidance provided by a more rapid molecular diagnosis was outweighed by the cost of isolating and treating PCR-positive/cytotoxin-negative patients. The costs, clinical consequences, and impact on nosocomial transmission of treating and/or isolating patients positive for toxigenic C. difficile by PCR but negative for in vivo toxin production merit further study.